Role of the apparent diffusion coefficient in the differential diagnosis of gastric wall thickening - Onur, Mehmet Ruhi; Ozturk, Fatma; Aygun, Cem; Poyraz, Ahmet Kursad; Ogur, Erkin (Wiley, 2012)
Purpose: To evaluate the role of the apparent diffusion coefficient (ADC) measurement made using diffusion-weighted magnetic resonance imaging (DWMRI) in the differential diagnosis of benign and malignant gastric wall thickening. Materials and Methods: Axial T2-weighted and DWMRI at b 600 and b 1000 s/mm2 gradients were performed in 94 patients (44 patients with gastric malignancy and 50 patients with benign gastric diseases) with gastric wall thickening which was detected by multidetector computed tomography (MDCT). The ADC values of the gastric lesions and healthy gastric walls in patients with gastric malignancies and in patients with benign gastric diseases were used in the differential diagnosis of benign and malignant lesions of the stomach. Results: The mean ADC values were lower in patients with gastric malignancies (1.62 +/- 0.57 and 1.40 +/- 0.33 at b 600 and b 1000, respectively) compared to those with healthy gastric walls (2.95 +/- 0.59 and 2.18 +/- 0.48) and benign gastric diseases (3.08 +/- 0.52 and 2.34 +/- 0.42) at b 600 and b 1000 gradients (P < 0.0001). Conclusion: The ADC measurement on DWMRI may be used to differentiate between benign and malignant gastric diseases. J. Magn. Reson. Imaging 2012;36:672677. (C) 2012 Wiley Periodicals, Inc.
Keywords: stomach; gastric cancer; DWI; ADC; MRI